An exploratory study on the factors that contributed significantly to the criminal behaviour of the first-time youth offenders enrolled in a life skills residential diversion programmes at Walter Sisulu Child and Youth Care Centre in Gauteng - Gule, Thembelihle Goodchild (Department of Social Development, 2021)
The overall aim of the study was to explore factors that could be associated with criminal behaviour of youth offenders diverted in the life skills residential diversion programmes at Walter Sisulu Child and Youth Care Centre, so as to contribute towards a better understanding of their profile. Therefore the study explored the participants' family backgrounds, the circumstances surrounding the committal of their offences and their responses to the offences they were diverted for in the life skills diversion programmes. An exploratory-descriptive type of a qualitative design was adopted in this study. A semistructured interview schedule was used as the research instrument for conducting in-depth face-to-face interviews with the participants. The study had one set of target population; who were 18 youth offenders (both male and female) between the ages 14-17 attending life skills residential diversion programmes at Walter Sisulu Child and Youth Care Centre. The profile of the participants seem to indicate that most of them had absent fathers and therefore lacked male figures who could act as role models. The study found that biological fathers of most participants were either deceased, whereabouts unknown, not involved in their financial maintenance or those who had stepfathers, had a bad relationship with them. The findings indicated that the participants' mothers were unavailable and therefore most participants were taken care of by their grandmothers. However, it seems most grandmothers often failed to supervise their grandchildren properly and as such it created an opportunity for the participants to be mischievous with no consequences for their behaviour. It was also found that violence in the family also contributed significantly to the aggressive criminal offences of some of the participants. Lastly, the study showed that the influence of drugs and negative peer pressure also played a significant role in the participants' involvement in criminal behaviour.